NURSING EDUCATION IN DEVELOPED COUNTRIES (KOREA AND GERMANY) - Namozova Umida Abdurafiq qizi; Sayfiyeva Nargiza Xusniddinovna (Web of Journals Publishing, 2026)
Nursing is an applied science based on natural sciences, humanities and social sciences, and has a unique knowledge base based on theoretical concepts such as human, environment, health and nursing. It is an applied study aimed at improving human health and well-being. The form of education in nursing is available at the secondary specialized and higher education levels, while nurses with secondary education are trained in medical colleges, while nurses with higher education are trained for professional activities in universities (universities and institutes).
Keywords: Nurse, university course, secondary specialized college course, NCLEX-RN exam, lecturing, exams.